RESISTENSI ORGANISASI PERANGKAT DAERAH PADA IMPLEMENTASI KEBIJAKAN E-PLANING DAN E-BUDGETING DI PEMERINTAH KABUPATEN PRINGSEWU - Wensi Hendriyani; Pitojo Budiono; Robi Cahyadi Kurniawan (P3M STISIPOL Dharma Wacana Metro, 2022)
Bureaucratic reform as a result of the industrial revolution 4.0 demands a change in work patterns in Regional Apparatus Organizations (OPD). Organizational change (OD) is an OD approach and technique through processes and technology for the planning, planning, direction and implementation of OD. E-planning and e-budgeting as an effort to synchronize regional and national policies and programs aim to create synergy between the regional and national economies. Changes in organizational policies that occur will be faced with resistance from individuals. Resistance as one of the causes of the lack of success of OD, it can be overcome by understanding resistance, planning and managing change effectively and efficiently. The purpose of the study was to determine the factors causing resistance and the magnitude of OPD resistance in the implementation of this policy. The research was conducted in Pringsewu Regency. The study used primary and secondary data and then analyzed using the Analytic Hierarchy Process. The results showed that the factors causing resistance were sequentially found in the priority criteria of HR, policies, behavior/attitudes, and SAPRAS. The magnitude of the resistance level of OPD in the implementation of e-planing and e-budgeting occurs in the criteria of HR (49.0%) which are influenced by alternative performance (26.8%), skills (14.7%), Bimtek (11.3%), Commitment (11.0%), ICT (10.9%), and SIMDA (8.7%). The most priority factor causing resistance to be improved is the handling of the quality of human resources (49.0%). The high level of HR resistance is due to ignorance and the lack of information received on change.